Low dose aspirin and cognitive function in the women's health study cognitive cohort. Issue 7601 (27th April 2007) - Kang, Jae Hee; Cook, Nancy; Manson, JoAnn; Buring, Julie E; Grodstein, Francine
Abstract : Objective To determine whether low dose aspirin protects women aged 65 or more against cognitive decline. Design Cohort study within both arms of the women's health study, a randomised, double blind, placebo controlled trial of low dose aspirin for the primary prevention of cardiovascular disease and cancer, 1992-5. Setting Women's health study, 1998-2004. Participants 6377 women aged 65 or more. Interventions Low dose aspirin (100 mg on alternate days) or placebo for a mean of 9.6 years. Main outcome measures Women had three cognitive assessments at two year intervals by telephone. The battery to assess cognition included five tests measuring general cognition, verbal memory, and category fluency. The primary prespecified outcome was a global score, averaging performance across all tests. The key secondary outcome was a verbal memory score, averaging performance on four measures of verbal memory. Results At the initial assessment (mean 5.6 years after randomisation) cognitive performance in the aspirin group was similar to that of the placebo group (mean difference in global score −0.01, 95% confidence interval −0.04 to 0.02). Mean decline in the global score from the first to the final cognitive assessment was also similar in the aspirin compared with placebo groups (mean difference 0.01, −0.02 to 0.04). The risk of substantial decline (in the worst 10th centile of decline) was also comparable between the groups (relative risk 0.92, 0.77 to 1.10). Findings were similar for verbal memory; however, a 20% lower risk was observed for decline in category fluency with aspirin (relative risk 0.80, 0.67 to 0.97). Conclusion Long term use of low dose aspirin does not provide overall benefits for cognition among generally healthy women aged 65 or more.